2014
DOI: 10.1128/mbio.01932-14
|View full text |Cite
|
Sign up to set email alerts
|

Improving Microbial Biogasoline Production in Escherichia coli Using Tolerance Engineering

Abstract: Engineering microbial hosts for the production of fungible fuels requires mitigation of limitations posed on the production capacity. One such limitation arises from the inherent toxicity of solvent-like biofuel compounds to production strains, such as Escherichia coli. Here we show the importance of host engineering for the production of short-chain alcohols by studying the overexpression of genes upregulated in response to exogenous isopentenol. Using systems biology data, we selected 40 genes that were upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 47 publications
0
89
0
Order By: Relevance
“…Interestingly, a recent study has implicated GidB in the improvement of microbial biogasoline production [122]. Isopentenol is an important target compound in pharmaceutical production, and is also a useable biofuel [123].…”
Section: Potential Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study has implicated GidB in the improvement of microbial biogasoline production [122]. Isopentenol is an important target compound in pharmaceutical production, and is also a useable biofuel [123].…”
Section: Potential Applicationsmentioning
confidence: 99%
“…The biggest challenge to microbial production of such compounds is the large amount of biomass needed to make large quantities, and isopentenol production in E. coli has shown to be relatively low [124,125]. The study by Foo et al identified 40 genes in E. coli that were up-regulated after exposure to isopentenol [122]. Of the 40 genes, gidB was one of six genes that increased both isopentenol tolerance and production in E. coli.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Considerable progress has been made in the production of isoprenol, a C5 alcohol derived from isopentenyl pyrophosphate (IPP), which is one of two universal precursors for isoprenoid compounds (George et al, 2015b;Zheng et al, 2013). In E. coli, the toxicity of both isoprenol (Foo et al, 2014) and IPP has been suggested to impact cell growth and limit product yields. Although the toxicity of IPP (and its longer chain derivatives GPP and FPP) was observed over a decade ago (Martin et al, 2003), a systematic assessment of this stress and its impact on host physiology has yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression at a t of 0.5 h shows that abrupt ferulate stress induces expression of genes encoding the efflux pump cphy1055-cphy1056, which is similar to E. coli mdlAB conferring resistance to organic solvents (21). Many of the genes upregulated at a t of 0.5 h are colocated in two genomic regions.…”
Section: Resultsmentioning
confidence: 98%